2022
DOI: 10.21203/rs.3.rs-2034285/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spontaneous, persistent T-cell dependent IFN-γ release in patients who progress to Long COVID

Abstract: After acute infection with Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), a significant proportion (0.2–30%) of patients experience persistent symptoms beyond 12 weeks, termed Long COVID. Understanding the mechanisms which cause this debilitating disease and identifying biomarkers for diagnostic, therapeutic and monitoring purposes is urgently required. Persistently high levels of IFN-γ were detected from peripheral blood mononuclear cells (PBMCs) of Long COVID patients using highly sensitive Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Krishna et al investigated the levels of IFN-γ from PBMCs of patients with LC and from patients who had recovered from acute COVID-19 infection [55].…”
Section: Testing-defined Clusters Of Lcmentioning
confidence: 99%
See 2 more Smart Citations
“…Krishna et al investigated the levels of IFN-γ from PBMCs of patients with LC and from patients who had recovered from acute COVID-19 infection [55].…”
Section: Testing-defined Clusters Of Lcmentioning
confidence: 99%
“…54 unexposed donor samples were recruited by the National Institute for Health Research BioResource Cambridge through the Anti-viral Responses in Ageing study before October 2019, so these patients were not exposed to SARS-CoV-2. 55 LC patients were recruited for the study based on LC symptoms that persisted for at least five months after acute COVID-19 [55].…”
Section: Testing-defined Clusters Of Lcmentioning
confidence: 99%
See 1 more Smart Citation
“…This persistence is critical as studies have shown that while antibody titers against SARS-CoV-2 decrease over time, the T-cell response, particularly memory T cells, remains more robust [155,158]. Interestingly, a significant proportion of LC patients retain T-cell responses to SARS-CoV-2 antigens months after recovery, even when antibodies are undetectable [159]. Also, no relationship was found between antibodies against the SARS-CoV-2 nucleocapsid antigen (protein N) and clinical LC symptomatology in a studied Danish population [160].…”
Section: The Relationship Of Long Covid To Systemic Low-grade Inflamm...mentioning
confidence: 99%
“…At present the cause of PASC remains elusive. However, there is a growing of evidence that PASC is associated with chronic inflammation [4][5][6][7][8][9][10][11][12] . For example, recently Cervia-Hasler 10 and colleagues demonstrated that at six months post-infection there was increased complement activation in PASC patients.…”
Section: Introductionmentioning
confidence: 99%